Doctors rostering system (DRS) / Siti Nur Aisyah Redzuan - Redzuan, Siti Nur Aisyah (2013)
Scheduling is an important part in working area because schedule is a technique that usually used to assign workload among staff. In Malaysia, in making the schedule is just by manually that is written up in Microsoft Excel and prints up then paste on the board. This is not a good technique where the schedule may easily lose and not easily retrieve if the staffs want to retrieve back the past schedule. In this research will focused on making the schedule and the doctor can update the schedule if the doctor cannot attend to work and the system will choose the available doctor to replace the doctor. Besides that, this application can help the doctor keep the schedule safe and can retrieve back the schedule. This system is just focused on 17doctors in Department of Surgery in Hospital Seberang Jaya, Pulau Pinang where the doctors have difficulty when the schedule is unsatisfied and unfair to the doctors. Although the schedule in this system was prepared by the admin but the doctor can easily change if unsatisfied or cannot attend to work. The system will choose the suitable and available doctor so that the other doctor still can come to work because the doctor has enough rest. For future work this system will give an alert message to the doctor if the schedule is change so that the doctor can refer back to the schedule what are the changes that have been made.